Pemanfaatan Pemanfaatan Kelimpahan Biomassa Eceng Gondok Rawapening sebagai Bahan Baku Briket Arang Campuran Tempurung Kelapa - Billah, Arif; Prayogo , Heri; Nugroho, Hadid Ady (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
The aim of the research is to develop charcoal briquettes made from a mixture of water hyacinth and coconut shells. This research approaches product development with stages: selecting raw materials, drying raw materials, charring, cleaning charcoal from impurities, making charcoal powder, binding charcoal powder, pressing and printing, and drying briquettes and characterization of the results. The equipment used includes: digital balance, ruler, vernier caliper, pressing and printing tools, oven, drum as a container for processing raw materials, smoothing or grinding tools, 80 mesh sieve, and LPG cylinder and stove. The ingredients used are water hyacinth (Eichhornia crassipes), coconut shell, starch or tapioca flour, and water. This research produced samples of 4 types of percentage composition composition between coconut shell and water hyacinth composition I (0% : 90%); II (25% : 65%); III (45% : 45%); and IV (65% : 25%) with the same percentage of adhesive for each composition, namely 10%. Compositions IV, III, II, and I show density values in order from largest to smallest, namely 0.5474 g/cm3; 0.5448 g/cm3; 0.4761 g/cm3; and 0.4126 g/cm3. Compositions II, III, I, and IV show the water content values in order from smallest to largest, namely 7.7556%; 7.8040%; 8.0366%; and 9.6544%. Compositions III, IV, II, and I show the combustion rate values in order from largest to smallest, namely 0.335 g/minute; 0.255 g/min; 0.230 g/min; and 0.202 g/min. Recommended ongoing research with the aim of optimizing the results of international standard charcoal briquettes; and expanding its usefulness, both for energy needs, supporting community economic growth as well as for environmental conservation. Keywords: Charcoal briquettes, coconut shells, water hyacinth